Real Exchange Rate Fundamentals: A Synthesis of the Literature - Ogun, Oluremi Davies (Journal of Reviews on Global Economics, 2019)
A general review of approaches to equilibrium real exchange rate was undertaken. The review covered most of the theoretical, methodological and empirical literatures that had been developed in the attempt to overcoming the measurement problems associated with the concept. The distinct approaches reviewed in the paper included, exchange rate equations with nominal and real disturbances, the purchasing power parity doctrine, productivity approach, macroeconomic balance, varieties of exchange rate equation models, and, behavioral equilibrium exchange rate approach. Although the models were generally theory-based and reasonably well motivated, a comprehensive evaluation of the appropriateness of some of the theoretically identified fundamentals might be a most desired status credibility check.